Efʿâlu’l-Kulûbta İlgâ ve Taʿlîk - Dinçer, Ferit (Muş Alparslan Üniversitesi, 2020)
Müslümanlar, Allah’ın (c.c.) kelâmı olan Kur’ân-ı Kerîmi daha sağlıklı ve doğru bir şekilde anlamak ve istifade etmek amacıyla, nazil olduğu dönemden günümüze dek, birçok ilim dalını meydana getirmişler ve bu alanda sa?yu gayrette bulunmuşlardır. Bu ilimlerden biri de Nahiv ilmidir. Âlimler, kelâmdaki nahvi, yemekteki tuza benzetmişler. Nahiv ilmin önemli bir bölümü de Zanne ve kardeşleri adlı fiillerdir. Bu fiiller ile ilgili bazı çalışmaların olduğunu bilmemize rağmen, böyle bir çalışmayı ele almamızın nedeni, anılan fiillere özgü olan ilgâ ve ta?lîk durumuna dikkat çekmektir. Çünkü Arap gramerinde önemli bir yere haiz olan ve Kur’ân’ın birçok yerinde de kullanılan Zanne ve kardeşleri, detaylı bir şekilde bilmek, Kur’ân-ı Kerîmi daha sağlıklı ve güzel bir şekilde anlamaya yardımcı olacaktır.

In order to understand and benefit from the Qur'an, which is the word of Allah (c.c.), in a healthier and more accurate way, Muslims have created many branches of science and made efforts in these areas. One of these sciences is undoubtedly nahiv. Because scholars compared the salt in the words to the salt in the meal. An important part of the discourse is the verbs called Zanne and her brothers. Although we know that there are some studies about Zanne and her siblings, the reason we consider such a study is to draw attention to the interest and adhesion situation that is specific to the verbs mentioned. Because knowing Zanne and her brothers, who have an important place in Arabic grammar and are used in many parts of the Qur'an, will help to understand the Qur'an, which is the main source of our religion, in a healthier and better way.
Drift and Ta?lîk in Ef?âlu’l-Clubs
anemon
Keywords: Zanne ve Kardeşleri; İlğa; Ta'lik; Nahiv İlmi; Ef?âlu’l-Kulûb; Nahiv Science; Zanne and her siblings; Ef'âlu'l-Cottage; İlgâ; Ta?lîk